Extracorporeal Carbon Dioxide Removal as an Alternative to Endotracheal Intubation for Non-Invasive Ventilation Failure in Acute Exacerbation of COPD. (October 2014) - Cole, Stephen; Barrett, Nicholas A; Glover, Guy; Langrish, Chris IS; Meadows, Chris; Daly, Kathleen; Agnew, Nicola; Gooby, Nigel; Ioannou, Nicholas
Extracorporeal carbon dioxide removal (ECCO2 R) is an efficient technique used in the management of hypercapnic respiratory failure. Its application in mechanically ventilated patients has been studied for over 30 years. We describe a case of severe, acute exacerbation of chronic obstructive pulmonary disease (AECOPD) unresponsive to non-invasive ventilation (NIV), where initiation of ECCO2 R was used effectively to prevent endotracheal intubation.